Intellectual Capital and Firm Value Evidence from Indonesian Companies: Kapital Intelektual dan Nilai Perusahaan: Bukti dari Perusahaan-Perusahaan Indonesia - Vivi Noviyanti; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Firm value represents a key indicator of corporate performance and market perception. Specific Background Intellectual capital has increasingly been recognized as an intangible resource that contributes to value creation in modern firms. Knowledge Gap Empirical findings regarding the relationship between intellectual capital and firm value remain inconsistent across sectors and periods. Aims This study aims to examine the relationship between intellectual capital and firm value based on empirical evidence from Indonesian companies. Results Using quantitative analysis, the findings indicate that intellectual capital demonstrates a significant association with firm value. Novelty This research provides updated empirical evidence on intellectual capital measurement within the Indonesian corporate context. Implications The results offer insights for companies and stakeholders in managing intellectual capital as part of strategic value creation. Keywords: Intellectual Capital, Firm Value, Financial Performance, Corporate Performance, Indonesia Key Findings Highlights: Intangible resources are empirically associated with market-based company valuation. Intellectual capital indicators show measurable links with corporate outcomes. Evidence supports the relevance of non-physical assets in value creation analysis.